Dung beetles (Coleoptera: Scarabaeoidea) population patterns in three environments in the Midwest of Brazil - Uchoa, Manoel Araécio; Rodrigues, Marino Miloca (EntomoBrasilis, 2019)
Abstract. Scarabaeids are economically very important due to their provision of several environmental services, in particular to cattle rearing, because they are highly active in the decomposition of cattle feces in pasture environments. The objectives of this research were to evaluate the season of dung beetle occurrence, and the effect of weather on their abundance and species richness in different environments. A total of 44,355 adults were captured: 105 samples in each of three different environments (agroecosystem, pasture and native forest), adding 315 samples for two consecutive years (November 2005 to November 2007). Fifty-three species were found in that three environments,being 51 of Scarabaeidae, including two subspecies of Dichotomius, and two of Hybosoridae: Coilodes humeralis (Mannerheim) and Coilodes sp.1. We verified a correlation between temperature and rainfall and the occurrence of Scarabaeidae species associated with bovine feces. The species with highest population levels were:Labarrus pseudolividus Balthasar in the pasture, and Ataenius platensis (Blanchard) in both: agroecosystem and native semi-deciduous forest. There was a positive correlation between higher temperature and rainfall with an increase in the abundance of adult dung beetles in the environments. The number of adults caught and species richness of dung beetles was significantly greater in the pasture when temperature and rainfall were higher. The combined analysis of the three environments showed that from Oct to Dec, when temperature and precipitation were highest, there was a significant increase in the capture of dung beetles in the traps in comparison to the period from Apr to Jul (coldest season). Esquemas populacionais dos escaravelhos (Coleoptera: Scarabaeoidea) em três ambientes no Centro-Oeste do Brasil Resumo. Scarabeídeos são economicamente muito importantes devido à pestação de vários serviços ambientais, em especial para bovinocultura, porque atuam fortemente na decomposição de fezes bovinas em ambientes de pastagem. Os objetivos desta pesquisa foram avaliar as épocas de ocorrência das espécies de besouros “rola bosta” e o efeito do clima sobre a abundância e riqueza de suas espécies em diferentes ambientes. Um total de 44.355 adultos foram capturados: 105 amostras em cada um dos diferentes ambientes (agroecossistema, pastagem e floresta nativa), somando 315 amostras durante dois anos consecutivos (novembro de 2005 a novembro de 2007). Cinquenta e três espécies foram encontradas nos três ambientes durante dois anos de amostragem, 51 de Scarabaeidae (incluindo duas subespécies de Dichotomius) e duas espécies de Hybosoridae: Coilodes humeralis (Mannerheim) e Coilodes sp.1. Houve correlação entre a temperatura e as chuvas com as épocas de ocorrência das espécies Scarabaeidae associadas com fezes bovinas. As espécies com níveis populacionais mais elevados foram: Labarrus pseudolividus Balthasar na pastagem e Ataenius platensis (Blanchard) em ambos: agroecossistema e floresta nativa semidecídua. Existe uma correlação positiva entre temperaturas mais elevadas e chuvas com aumento na captura dos “rola bosta” em armadilhas. O número de adultos capturados e a riqueza em espécies dos “rola bosta” capturados foi significativamente superior quando a temperatura e a pluviosidade foram mais altas. A análise combinada dos três ambientes mostrou que de outubro a dezembro, quando a temperatura e a precipitação foram mais elevadas, houve um aumento significativo na captura destes besouros nas armadilhas.